The Performance and Efficiency of Zakat Institutions in Jambi - Desi Retnowati (Center of Strategic Studies (PUSKAS) BAZNAS, 2018)
Zakat is the third pillar of Islam and has socio-economic impacts. In practice, zakat institutionshave limitations with regard totheir institutional and managerial aspects, which result in them not achiveing optimum performance and efficiency. This research aims to analyzethe performance and efficiency of zakat institutions in Jambi Province. This research measures the performance of zakat institutions through the institutional indicators of the National Zakat Index (NZI), and it measures theirefficiency using theData Envelopment Analysis (DEA) method. The samples used in this research are BAZNAS Jambi Province and LAZ RSIM. Based on the results of the performance analysis, BAZNAS Jambi hadan index value of 0.44, and LAZ RSIM hadan index value of 0.63,which classified the performance of the zakat institutionsas “fairly good”to“good.” Based on the results of the efficiency analysis, LAZ RSIM has reached the maximum level of 100% efficiency. BAZNAS Jambi Province is operating at56.1% efficiency. The average efficiency for the combined zakat institutions is 78.1%. Keywords: performance, efficiency, national zakat index (NZI), data envelopment analysis (DEA)